Cortical Thickness in Pre Central and Post Central Human Brain Cortex of Patient with Headache: MRI finding (Medico Legal Update, 2021)
It is new clear that the brain of the headache sufferers are different from those of people without headache, theimaging study showed thickening in specific area of brain related to communication of sensory processingcalled somatosensory cortex (post central region) in this study we examine 36 patient, 28 of them haveheadache of variable duration, 8 healthy patient used as control (i.e. has no headache). The result has foundthat the cortex area of brain is thicker in pre central and post central cortex, especially predominant in postcentral cortex and this thickening isincreasing with duration of headache and not related to the age of patient,the explanation of these structural changes will be discussed in this study